Analysis of Perceptions of UIN Sunan Ampel Surabaya Students Regarding the Existence of Sharia Banking - Isnaini Maulidatu Nisa’; Muhammad Yazid (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Indonesia operates a dual banking system, namely a conventional banking system using an interest rate system and Islamic banking with a profit-sharing system. The growth of Islamic banks has not been able to keep up with conventional banks. This can be seen from the low market share of Islamic finance. There needs to be a strategy and model to increase public understanding of Islamic banks. The